Estimation of Reliability for a Two Component Survival Stress-Strength Model. (18th August 2011) - Munoli, S. B.; Mutkekar, Rohit R.
Abstract : The reliability function for a parallel system of two identical components is derived from a stress-strength model, where failure of one component increases the stress on the surviving component of the system. The Maximum Likelihood Estimators of parameters and their asymptotic distribution are obtained. Further the Maximum Likelihood Estimator and Bayes Estimator of reliability function are obtained using the data from a life-testing experiment. Computation of estimators is illustrated through simulation study.